Structural and diagenetic signatures of a very shallow sub-volcanic intrusion into a carbonate platform (Albian, Basque-Cantabrian Basin, Northern Spain). (April 2023) - Pascault, Ophélie; Durlet, Christophe; Teboul, Pierre-Alexandre; Ducoux, Maxime; Girard, Jean-Pierre; Virgone, Aurélien; Saucède, Thomas
Abstract: In several tectonic contexts and especially in hyper-extensive basins, magmatic rise may crosscut shallow marine carbonate series, forming either volcanic systems or only igneous intrusions at various depths. Impacts of these magmatic events on the surrounding carbonate sediments can be significant and are relatively well documented from a geometrical, sedimentological and hydrochemical point of view. Their diagenetic signature (e.g., early diagenetic phases in cases where magma reaches or approaches the surface) still remains poorly investigated. In this paper the authors use a multi-proxy approach combining morpho-structural, diagenetic (cement stratigraphy), geochemical (carbon and oxygen isotope, U–Pb dating) and sedimentological study to investigate the Larrano igneous body contemporaneous with the Urgonian limestones (Early Albian) of the Duranguesado platform, in the well-preserved and hyper-extended Basque-Cantabrian Basin. This investigative work produced several results: the first result, combining morpho-structural and sedimentological data, is the model of a basaltic magma rising along normal faults but stopping about 50 m below the paleo-seafloor; another is the detailed description the "Larrano eogenetic anomaly" that includes cataclastic fractures, dissolution, Fe oxy-hydroxides, ferroan saddle dolomite and magnesian calcite. Such phases form an early diagenetic overprint around the igneous body and testify to the thermal shock and warm seawater circulation occurring at the time of and just after the intrusion. Pre-intrusive and post-intrusive hydrothermally-influenced cements and facies are also recorded and are perfectly calibrated by a detailed cement stratigraphy associated with a layering model of the sedimentary units. The role of magmatic CO2 contribution is not quantified in the present study. Furthermore, the δ 13 C signature of various cements, micrites and bioclasts suggests no thermogenic methane contribution, unlike other Albian magmatic intrusions hosted by different lithologies and recorded at various depths below the paleo-seafloor. Highlights: For the first time, early diagenetic signature of a very shallow sub-volcanic intrusion in carbonate platform is reported. The igneous body investigated in this paper intrudes an Urgonian carbonate platform of the Early Albian. The intrusion is located along a synsedimentary fault of the hyper-extended Basque-Cantabrian Basin. Structural, early diagenetic and geochemical data indicates an intrusion emplacement just below the paleo-seafloor (~50m). Pre- & post-intrusive hydrothermal circulations affecting early cements and specific facies related to seeps are reported.